Independent Risk Factors for Deaths due to AIDS in Chongqing, China: Does Age Matter? - Zhou, Yihong; Yang, Zhongping; Liu, Min; Lu, Yanqiu; Qin, Yuanyuan; He, Xiaoqing; Zeng, Yanming; Harypursat, Vijay; Chen, Yaokai (Frontiers in Medicine, 2021)
Background: People living with HIV (PLWH) are aging worldwide, and different management strategies may be required for older and younger PLWH. However, demographic characteristics, illness distribution, mortality, and independent risk factors in the PLWH population in China are not yet fully understood, especially in patients aged 50 years or older. Methods: We conducted a retrospective analysis of 4445 HIV-positive Chinese inpatients in Chongqing, China. Results: The mortality rate in patients 50 years or older (the older group) was significantly higher than that in those under 50 years (the younger group) (p <0.001). In the younger group, independent risk factors for death included: nadir CD4+ T-cell counts <200 cells/μL, not owning medical healthcare insurance, not being on cART, injection drug use, and having one of the following comorbidities: Pneumocystis pneumonia, cryptococcal meningitis, AIDS malignancy, non-AIDS malignancy, and kidney disease. In the older group, independent predictors of death included: being urban residents, nadir CD4+ T-cell counts <200cells/μL, not being on cART, and having comorbidities such as Pneumocystis pneumonia, hepatitis C, talaromycosis, non-AIDS malignancy, and kidney disease. Conclusions: Demographic characteristics, illness distribution, mortality, and independent risk factors for death in HIV-positive patients differ between the older group and the younger group, indicating that a changing suite of medical and allied support services may be required the for management of older PLWH.